A Praxis of Reading Strategies in Twenty-First Century Learning: Beyond the Group Work - Rozanah Katrina Herda; Leong Jin Jee (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2024)
The multifaceted problems in EFL reading classrooms are due to the limitation of students' L2 mastery. One of them is EFL students, who are expected to be lifelong readers and must always be ready to face the challenges of the global society. As one of the core skills of 21st-century learning, collaboration is emphasized in reading classrooms to teach the EFL students learning English texts. This study was a quasi-experimental study with a One-Group Pretest-Posttest design with two research questions: 1) What is the EFL students need in reading class? 2) Is there a significant difference between the mean scores of the pretest and the posttest in reading performance obtained by EFL students using CSR? The participants of this study were 68 students in a Senior High School in Yogyakarta, Indonesia. Online questionnaires and Pretest-Posttest were used to collect the data. As a result, the need analysis revealed three crucial things: needs for the atmosphere and strategy in reading class, a situation in their typical reading class, and a desire to have collaborative reading. Therefore, the pretest and posttest showed that the use of CSR significantly improved their reading skills in a collaborative atmosphere. Furthermore, their perspectives on using CSR were positive, for they experienced reading collaboratively. Each reading phase has a relevant comprehension strategy: Preview, Click and Clunk, Get the Gist, and Wrap up. The study gives pedagogical effect to the EFL teachers who want to innovate their reading class and help students overcome their problems, especially struggling readers.